The Role Of Financial Literacy, Risk-Taking Behavior, And Business Networking On Start-Up Growth - Efendi; Harahap, Subur; Hidayat, Riyan; Mardhotillah, Bunga (Journal Management & Economics Review (JUMPER), 2025)
This study investigates the role of financial literacy, risk-taking behavior, and business networking on the growth of start-ups in Indonesia. Using a purposive sample of 200 start-up entrepreneurs from diverse sectors, data were collected through an online questionnaire and analyzed using multiple linear regression. The results indicate that all three variables significantly and positively influence start-up growth, with business networking having the strongest impact, followed by financial literacy and risk-taking behavior. These findings emphasize the importance of not only financial skills and entrepreneurial mindset but also the strategic use of social networks in fostering business expansion. Practical implications for entrepreneurial training, ecosystem development, and policy formulation are discussed. The study contributes to the understanding of start-up success factors in emerging economies and offers directions for future research.